THE INFLUENCE OF MINIMAL SENTENCE PAIRS TOWARDS STUDENTS‟ TENSES MASTERY AT THE SECOND SEMESTER OF THE EIGHTH CLASS OF SMP NEGERI 19 BANDAR LAMPUNG - Febriyanti, Febriyanti (Lentera: Jurnal Ilmiah Kependidikan, 2015)
Student‟s tenses matery is influenced by many factors. One of them is the technique which the teacher uses in teaching. The research applied Minimal Sentence Pairs in teaching tenses in the classroom. Then, it analyzed the result of the technique in order to know its influence.The research was conducted at the second semester of the eighth class of SMP Negeri 19 Bandar Lampung. The students of 8C was as experimental class that was taught by Minimal Sentence Pairs and 8D was as control class that was taught by Conventional Technique. The samples were taken based on cluster random sampling technique. To analyze the data, this research used experimental method by using t-test formula.The result shows that there is positive influence of Minimal Sentence Pairs towards students‟ tensen mastery at the second semester of the eighth class of SMP Negeri 19 Bandar Lampung. It is shown from distribution list with dk=78 obtained the tratio is t0.975 or significant level of 5% and tratio t0.95 and significant level of 1% equals to 2.00 and 1.67. They are smaller than tcal (t-test) = 11.86. The average score of the students‟ tenses mastery who are taught by minimal sentence pairs X1= 81.73 is higher than who are taught by conventional technique X2= 53.15.